String Bog or "Strangmoor" in Cedarburg Bog - (:unkn) unknown (My University, 1984)
This paper discusses the string bog portion of Cedarburg Bog and the origin of string bogs in general. String bog or "strangmoor" Is found in Cedarburg Bog, which Is about 200 miles south of the southernmost string bog location previously reported. The string bog Is deep within the bog, remote from both the periphery of the bog and the open lakes within It. This vegetational pattern consists of slightly raised ridges and islands with woody vegetation, alternating with flat sedge mat areas. This string bog, like others of North America and Eurasia, is found on a slightly sloping surface; the alternating ridges and flats are at right angles to the slope of the peat surface and the apparent direction of water flow. This orientation has given rise to various explanations concerning the origin of these patterns.
Keywords: string bog; Cedarburg Bog